ANALISIS PRAANGGAPAN WACANA IKLAN PADA PRODUK KECANTIKAN KATALOG WARDAH EDISI PRICELIST BEST SELLER - Almas Nopiyanti; Mutia Febriyana (Universitas Islam Sumatera Utara, 2022)
Advertising is a form of communication that has an important role to introduce a product in the form of goods and services to the public. Various forms of attractive and creative advertisements in print and electronic media give rise to phenomena in advertising, giving rise to a new lifestyle. It can be interpreted as an advertising effort to always highlight the advantages of the advertised product. Therefore, advertisers try to convey advertisements well so that they can be accepted by consumers. The research method used in this study is a pragmatic study research method. This research is a descriptive study with qualitative data analysis. This study focuses on beauty advertising utterances that contain presuppositions. The data of this research is advertising speech in the best seller pricelist wardahedition beauty catalog which contains presuppositions. The data source of this research is advertisement speech from several advertisements in the best seller pricelist edition of Wardah beauty catalog. The research instrument is carried out in the form of documentation and notes. The results of the research data analysis used an informal presentation.